ION TRANSFER ANALYSIS OF EPHEDRINIUM ION AT LIQUID- LIQUID INTERFACE USING VOLTAMMETRY - Irdhawati
Ephedrine hydrochloride [(1R-2S)-2-(methylamino)-1-phenylpropane-1-ol hydrochloride (Eph HCl) is a sympathomimetic drug that stimulates both - and -adrenergic receptors. It causes a rise of systolic and diastolic pressure, bronchodilation and mild stimulation of the central nervous system.